First Report of Variant BCL6 Gene Rearrangement; Inversion 3: Clinical Presentation in a Rare Entity of Splenic B-Cell Lymphoma/Leukemia with Prominent Nucleoli - Abunaser, Suhaib M. A.; Pais, Anurita; Ibrahim, Rehab H. M.; Zaidi, Uzma; Butti, Noora M. (Indian Journal of Medical and Paediatric Oncology, 2025)
Splenic B cell lymphoma/leukemia with prominent nucleoli (SBLPN), previously known as hairy cell leukemia variant (HCL-V), remains a rare and provisional entity within the spectrum of splenic B cell neoplasms. It demonstrates overlapping morphologic and immunophenotypic features with low-grade B cell lymphomas, posing diagnostic and therapeutic challenges. We report the first case of inversion 3q27 causing a variant BCL6 gene rearrangement within a complex clonal karyotype, characterized by multiple copy number alterations, that is, duplication 1q, deletion 7p, partial trisomy 8q, deletion 9q, deletion 10p, isochromosome 14q, trisomy 18, and trisomy X, indicative of marked genomic instability in a rare entity of SBLPN. The aggressive clinical course observed further emphasizes the need for comprehensive diagnostic workups for prognostication. As exact defining genetic alterations are not yet established for this entity, expanding the cytogenetic and molecular landscape is crucial for refining classification, prognostication, and therapeutic strategies. The case illustrates how genetic complexity may drive disease aggressiveness and management challenges, underscoring the need for early multidisciplinary interventions and individualized treatment strategies.
Keywords: HCLv; SBLPN; complex karyotype; chromosome 3q27 inversion; variant BCL6 gene rearrangement; fluorescence in situ hybridization